Recontextualizing the Role of Social Media in the Formation of Filter Bubbles - Papp János Tamás (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2023)
One relatively popular area of scientific research on the social impact of social media is the phenomenon of filter bubbles and echo chambers. This notwithstanding, the true meaning of these concepts has not been precisely determined to date, and the social effects of the phenomena continue to be surrounded by heated debates. In this article, I briefly shed light on the contradictions underlying the theoretical and practical substantiation of filter bubbles and echo chambers. While the emergence of the phenomenon of filter bubbles seems logical from a theoretical point of view, its true presence cannot be discerned in reality. One reason for this is the user’s autonomous filtering activity, another reason is the widely available, diverse media environment. The social polarization that is increasingly experienced today emerged in the mutual interaction of traditional and online media: in the attention-based media environment promoted by the Internet, traditional has media became more and more opinion-based, increasing the possibility of personalization, a process that was further exacerbated by social media. As a result, the press moved towards a more polarized content production. Besides describing this process, in this paper I analyze the EU’s Digital Services Act focusing on the solutions it offers to the problem of recommendation systems and filter bubbles. Finally, I explore the question how quality news media content could help burst personal filter bubbles.